PENGEMBANGAN LKS ILMU PENGETAHUAN ALAM KELAS 4 MELALUI PENDEKATAN INTEGRASI AL-ASMA' AL-HUSNA - Alfan Nur Azizi (Universitas Islam Malang, 2021)
The development of students' worksheets of science with Al-Asma’ Al-Husna approach was based on the need for students’ worksheets with Al-Asma’ Al-Husna integration as one of students' learning resources. This research aims to fulfill student worksheets' availability to increase elementary school students' effectiveness. The purpose of this research was to produce students' worksheets of science for 4th grade by Al-Asma’ Al-Husna integration approach. This study used the development research method. According to the validators' assessment, the result of validation by matter experts was in good qualifications, the result of validation by design expert was also in good qualifications. The attractiveness assessment by students shows the results that the students’ worksheet was interesting. Meanwhile, the test results were carried out using the pre-test and post-test methods which showed a positive effect. Overall, the science students' worksheets were included in both qualifyings so fit for science teaching for fourth grade in elementary school.